(untitled) (Proceedings of International Educators Conference, 2023)
Inherent in every human society is science. One of the most pervasive and poorly defined ideas is contemporary science is . It is clear that science is fundamentally an illusive idea that is much simpler to feel than to explain. In this article, one approach to investigating the idea is taken into account through the technique of paremiological stock analysis, which includes a variety of proverbs.